(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Aims: This study evaluated the relationship between demographic variables, location, histopathologic results with Eyelid Tumors in Labbafinejad hospital in Tehran from 2010 to 2020. Methods and Material: The t-test and analysis of variance were used for comparison of normally distributed variables among groups. Results: The study was performed on 97 men and 115 women, in which we found 88 cases of benign tumors and 124 cases of malignant tumors. The mean age of the patients was 51.04± 22.9 years ranged between 1- 89. The topography analysis of lesions showed the frequency of locations: 98 cases at the lower eyelid, 112 cases at the upper eyelid, and 2 on both sides, 107 cases at the right eyelid, 101 cases at the left eyelid, and 4 in both eyelids. We realized that basal cell carcinoma was the most frequent malignancy reported, followed by squamous cell carcinoma, whereas intradermal nevus and dermoid cyst made up most of the benign lesions, respectively. Our data also demonstrated a significant difference in the number of men diagnosed over women with basal cell carcinoma. Conclusions: In this study, 54.8% of lesions were malignant, found mostly in men. The top two types of malignant tumors were basal cell carcinoma and squamous cell carcinoma, and the most frequent benign lesions were intradermal nevus and dermoid cyst, respectively.